Outcome of conscious survivors of out-of-hospital cardiac arrest. (December 2018) - Slapnik, Eva; Rauber, Martin; Kocjancic, Spela Tadel; Jazbec, Anja; Noc, Marko; Radsel, Peter
Abstract: Aim: Only up to 20% of patients with out-of-hospital cardiac arrest (OHCA) receive immediate and optimal initial cardiac resuscitation and consequently regain consciousness soon after return of spontaneous circulation (ROSC). In the present study, we compared the outcome of conscious survivors of OHCA presenting with ST-elevation myocardial infarction (STEMI) in post-resuscitation electrocardiogram undergoing immediate invasive coronary strategy with randomly selected STEMI patients without preceding OHCA undergoing primary PCI. Methods: We conducted a single-centre registry-based analysis of all conscious OHCA survivors with STEMI over the last 10 year period. We gathered clinical and angiographic data and compared them with a randomly selected cohort of non−OHCA patients with STEMI within the same period. Patients were matched by sex, age and STEMI location. Results: 86 conscious survivors of OHCA were admitted between 2006 and 2016. OHCA was witnessed in all patients (85% EMS witnessed), and all patients presented with initial shockable rhythm. Clinical and angiographic features were well matched with randomly selected STEMI patients without OHCA presenting to our department within the same study period. Delay from symptoms to EMS arrival but not delay from EMS to PCI was significantly shorter in conscious OHCA survivors (1.2 ± 1.3 h vs 3.1 ± 3.8 h, p < 0.001), yielding decreased total myocardial ischemic time (2.6 ± 1.3 h vs 4.6 ± 4.0 h, p < 0.001). Hospital and 1-year survival with normal neurological condition in conscious survivors of OHCA (cerebral performance category 1) was excellent and numerically even better than survival of STEMI patients without OHCA. Conclusion: Conscious survivors of OHCA with STEMI have excellent survival if they undergo immediate invasive coronary strategy. Since there is no obvious post-resuscitation brain injury in this subgroup of OHCA patients, it is probably shorter duration of myocardial ischemia driven by shorter delay from symptoms to EMS arrival that contributes to the good outcome, which is at least similar to STEMI patients without OHCA.